Leadership for the Future Lessons from the Past, Current Approaches, and Future Insights. - Mengel, Thomas (Cambridge Scholars Publisher, 2021)
This volume explores various approaches to leadership from both the past and the present, critically analysing these in the light of possible future challenges and scenarios. In addition, by drawing from the field of future studies, it introduces the reader to concepts of leadership that are 'future-ready'.